An Unusual Case of Rapidly Progressive Hyperbilirubinemia - Kimberly M. Thornton; Michael F. Nyp; Lejla Music Aplenc; Gary L. Jones; Shannon L. Carpenter; Erin M. Guest; Steven M. Shapiro; Winston M. Manimtim (Case Reports in Pediatrics)
We present an unusual case of hyperbilirubinemia with rapid early progression leading to bilirubin encephalopathy in a term neonate. Despite early recognition and intervention, the total serum bilirubin reached a maximum level of 39 mg/dL at 32 hours of life. Prior to an emergent exchange transfusion, the patient’s diagnostic evaluation was significant for Coombs-negative microangiopathic hemolytic anemia and thrombocytopenia. Further testing revealed a deficiency of ADAMTS13 protein, or von Willebrand factor-cleaving protease, a finding diagnostic of congenital thrombotic thrombocytopenic purpura, or Upshaw-Schulman syndrome. This rare disease is often misdiagnosed, especially in the newborn period.